"After having a waterbirth, I feel like it's the only way people should deliver babies": The decision making process of women who plan a waterbirth. (March 2020) - Fair, Cynthia D.; Crawford, Alyssa; Houpt, Bethany; Latham, Vicki
Abstract: Objective: To explore the decision making process of women who seek to give birth in water Design: A qualitative design using semi-structured interviews with women who planned a waterbirth was used. Interviews were recorded, transcribed, and coded for emergent themes using a grounded theory approach for analyses Setting: Twenty-three women (mean age = 33.5 years mean number of children = 2.5) who had planned a waterbirth were recruited from a prenatal care clinic in a mid-sized southeastern city in the United States. Questions explored how they decided to pursue a waterbirth, sources of information, support systems, resistance, and their birth experience Findings: Although all participants used the tub during labor, five did not give birth in the water. Analyses revealed that a belief in their body's ability to give birth along with the desire for limited medical interventions were the primary reasons for choosing waterbirth. Previous positive and negative experiences with birth also shaped their decision. Women actively sought information about waterbirths from the internet and friends. One-third of participants decided to pursue a waterbirth later in pregnancy and changed OB practices in order to have access to a waterbirth. Midwives and doulas were viewed as critical supporters of their waterbirth decision. However, most participants experienced some form of resistance toward their decision from others including family, friends, coworkers, and strangers. The overwhelming majority were positive about their experience and indicated they felt empowered, even if they were unable to give birth in the water, and encouraged other women to consider waterbirth. Most indicated they wanted to have a waterbirth in the future.